Tracking the Migration of Injectable Microdevices in the Rodent Brain Using a 9.4T Magnetic Resonance Imaging Scanner - Khalifa, Adam; Weigand-Whittier, Jonah; Farrar, Christian T.; Cash, Sydney (Frontiers in Neuroscience, 2021)
Wirelessly powered microdevices are being miniaturized to improve safety, longevity, and spatial resolution in a wide range of biomedical applications. Some wireless microdevices have reached a point where they can be injected whole into the central nervous system. However, the state-of-the-art floating microdevices have not yet been tested in chronic brain applications, and there is a growing concern that the implants might migrate through neural tissue over time. Using a 9.4T MRI scanner, we attempt to address the migration question by tracking ultra-small devices injected in different areas of the brain (cortico-subcortical) of rats over 5 months. We demonstrate that injectable microdevices smaller than 0.01 mm3 remain anchored in the brain at the targeted injection site over this time period. Based on CD68 (microglia) and GFAP (astrocytes) immunoreactivity to the microdevice, we hypothesize that glial scar formation is preventing the migration of chronically implanted microdevices in the brain over time.